TELHADOS E FACHADAS VERDES SÃO ELEMENTOS DE ABSORÇÃO ACÚSTICA? - Ruocco, Pedro Pimentel; Silva, Priscila Weruska Stark da; Michalski, Ranny Loureiro Xavier Nascimento (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The vegetation incorporated into buildings, as green walls and green facades, has a very significant effect on the urban microclimate, and it has also an importance on the acoustic absorption of the urban noise. There are some variables which interfere on this capacity of sound absorption: the vegetation, the substrate and the moisture, for example. To better understand the real impacts of the sound absorption through these greenery elements, it was done an extensive bibliographic review and it was possible to conclude the indeed ability of the green roofs and the green facades to absorb the noise, resulting in an acoustic gain for the urban mesh. Other studies will be conducted to measure and compare the acoustic absorption capacity of these greenery systems, in order to show up its influence and benefits.